Adverse Events Following Immunizations in Infants Under 1 Year of Age in Lorestan Province, Western Iran - Anbari Khatereh; Ghanadi Koruosh; Toulabipour Alireza; Jamebozuorghi Daryuosh; Baharvand Parastoo (Korean Society for Preventive Medicine, 2023)
Objectives Vaccination is an important intervention for preventing disease and reducing disease severity. Universal vaccination programs have significantly reduced the incidence of many dangerous diseases among children worldwide. This study investigated the side effects after immunization in infants under 1 year of age in Lorestan Province, western Iran. Methods This descriptive analytical study included data from all children <1 year old in Lorestan Province, Iran who were vaccinated according to the national schedule in 2020 and had an adverse event following immunization (AEFI). Data were extracted from 1084 forms on age, sex, birth weight, type of birth, AEFI type, vaccine type, and time of vaccination. Descriptive statistics (frequency, percentage) were calculated, and the chi-square test and Fisher exact test were used to assess differences in AEFIs according to the above-listed variables. Results The most frequent AEFIs were high fever (n=386, 35.6%), mild local reaction (n=341, 31.5%), and swelling and pain (n=121, 11.2%). The least common AEFIs were encephalitis (n=1, 0.1%), convulsion (n=2, 0.2%), and nodules (n=3, 0.3%). Girls and boys only showed significant differences in mild local reactions (p=0.044) and skin allergies (p=0.002). The incidence of lymphadenitis (p<0.001), severe local reaction (p<0.001), mild local reaction (p=0.007), fainting (p=0.032), swelling and pain (p=0.006), high fever (p=0.005), and nodules (p<0.001) showed significant differences based on age at vaccination. Conclusions Immunization is a fundamental public health policy for controlling vaccine-preventable infectious diseases. Although vaccines such as the Bacillus Calmette-Guérin vaccine, oral poliovirus vaccine, and pentavalent vaccine are well-researched and reliable, AEFIs are inevitable.